Sertaconazole in the treatment of vulvovaginal candidiasis - Z. N. Efendieva (Медицинский совет, 2019)
Vulvovaginal candidiasis today is one of the most pressing problems in the field of women’s health. However, the prevalence of Candida with formed drug resistance to fluconazole significantly complicates the treatment of this disease. Thus, the evaluation of the safety and efficacy of other antimycotic drugs becomes an important task in the fight against recurrent genital candidiasis. The article presents the data of international and domestic studies on the possibilities of using sertaconazole in the therapy of vulvovaginal candidiasis.